Implementasi Pengelolaan Administrasi Kesiswaan Sekolah SD IT Islamic Centre - ADeana, Fadillah Putri; Berutu, Sri Rahmayanti; Harahap, Hasima; Aziz, Mursal (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Student administration management has a very important role, because student administration management can develop the abilities and potential of quality students in accordance with educational goals. This article analyzes the implementation of student administration management at the SD IT Islamic Center school with a study formulation, namely first, student administration management at the SD IT Islamic Center, second, library services at the SD IT Islamic Center. The purpose of writing this research is to examine the extent of the implementation of student administration management at the Islamic Center IT Elementary School. To obtain research results, this research uses descriptive qualitative methods using data collection instruments, namely observation, interviews and documentation. The results of this research show firstly, the management of student administration at SD IT Islamic Center, where there are five student administration management which are important points, including the acceptance of new students, coaching students, grouping students, data collection on student learning progress, and guidance. and student counseling. Second, there are three library services at the SD IT Islamic Center, including library material lending services, reference services, and reading room facilities/circulation services.